2014
DOI: 10.1111/papt.12022
|View full text |Cite
|
Sign up to set email alerts
|

Zone of proximal development (ZPD) as an ability to play in psychotherapy: A theory‐building case study of very brief therapy

Abstract: Accessing very problematic content may be very difficult even though the client's ability to mentalize other material appears ordinary. Mildly depressed clients who have developed powerful care-taking coping strategies may not respond to very brief therapeutic interventions. A client's minimal acknowledgements may mislead the therapist into supplementing the client's failing self-reflection rather than addressing the issue that provokes this failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The concept appears to have wide applicability, from depression (as in the present study) and anxiety (Meystre, Kramer, De Roten, Despland, & Stiles, 2014) to personality disorders (Dimaggio & Lysaker, 2015) and even neurological assessments (Tikkanen, Stiles, & Leiman, 2011). It may vary in breadth; an overly narrow TZPD may impede therapeutic work (Zonzi et al, 2014). It refers to many of the same sort of observations as the concept reflective or mentalization capacity, which is considered as a limiting factor in the treatment of serious disorders such as borderline personality disorder (Bateman & Fonagy, 2010) and psychosis (Lysaker & Dimaggio, 2014), though it adds the suggestions that the zone (capacity) may be specific to particular content and that it may shift during successful therapy.…”
Section: The Therapeutic Zone Of Proximal Development and Ambivalencementioning
confidence: 64%
“…The concept appears to have wide applicability, from depression (as in the present study) and anxiety (Meystre, Kramer, De Roten, Despland, & Stiles, 2014) to personality disorders (Dimaggio & Lysaker, 2015) and even neurological assessments (Tikkanen, Stiles, & Leiman, 2011). It may vary in breadth; an overly narrow TZPD may impede therapeutic work (Zonzi et al, 2014). It refers to many of the same sort of observations as the concept reflective or mentalization capacity, which is considered as a limiting factor in the treatment of serious disorders such as borderline personality disorder (Bateman & Fonagy, 2010) and psychosis (Lysaker & Dimaggio, 2014), though it adds the suggestions that the zone (capacity) may be specific to particular content and that it may shift during successful therapy.…”
Section: The Therapeutic Zone Of Proximal Development and Ambivalencementioning
confidence: 64%
“…In successful cases, therapeutic collaboration should encourage the movement of the client's ZPD as therapy progresses (Ribeiro et al, 2013;Zonzi et al, 2014);…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have supported and elaborated this conceptualization (Caro Gabalda & Stiles, 2013;Meystre, Kramer, De Roten, Despland, & Stiles, 2014;Ribeiro et al, 2014a;Ribeiro, Ribeiro, Gonçalves, Horvath, & Stiles, 2013;Zonzi et al, 2014). The studies have identified several ways a client may signal that the TZPD has been exceeded, including APES setbacks and invalidation of the intervention.…”
mentioning
confidence: 97%